Pengaruh Disiplin Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT. HAHA Spektrum Indonesia Depok - Indah Sulistyawati; Rosento Rosento (Universitas 45 Surabaya, 2024)
This research is to determine the effect of Work Discipline and Job Satisfaction on Employee Performance at PT. HAHA Indonesian Spectrum. The research design used by the author uses quantitative methods. The sampling technique uses a saturated sampling technique. Data collection for the results of respondents' answers in the questionnaire used a Likert scale. The total sample is 40 employees at PT. HAHA Spektrum Indonesia and tested using SPSS Version 20. The results of the hypothesis test calculation obtained an F value of 11.191. It can be concluded that the hypothesis (H3) states that there is a positive and significant influence between work discipline and job satisfaction on the performance of PT employees. HAHA Indonesian Spectrum. This is because the calculated F value of 11.191 is greater than the F table of 3.250. And it is supported by a significant value of 0.000 where the condition for accepting this hypothesis is a significant value of less than 0.05. From the test results between the independent variables, namely work discipline and job satisfaction with the dependent variable, namely employee performance, it can be seen that F count is (11.191) F table (3.250) and a significant value of 0.000 < 0.05.